2019
DOI: 10.21608/ajs.2019.43550
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Evaluation of Encapsulated Probiotic Bacteria Supplementation to Ruminant Rations

Abstract: The aim of this study was to in-vitro evaluate encapsulated probiotic supplementation to ruminant rationson degradation and fermentation parameters. The ration consisted of 40% alfalfa hay and 60% concentrate feed mixture. Encapsulated and not encapsulated probiotic were supplemented with level of 10 6 cfu/kg of the total dry matter of ration (DM) and compared with encapsulation media (Sodium Alginate, SA) and control (not supplemented ration). DM and OM degradation and total gas production as well as fermenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…That indicates using probiotic additive with camels can stimulate rumen microorganism which resulted in increasing IVDMD%. Makled et al (2019) found that using probiotic (Lactobacilli isolates with 10 6 cfu/ kg DM) in in vitro evaluation (alfalfa hay and CFM, R:C= 40:60) increased IVDMD from 43.21% to 46.45% in control and probiotic groups, respectively.…”
Section: In Vitro Dry Matter Disappearance (Ivdmd%)mentioning
confidence: 97%
See 2 more Smart Citations
“…That indicates using probiotic additive with camels can stimulate rumen microorganism which resulted in increasing IVDMD%. Makled et al (2019) found that using probiotic (Lactobacilli isolates with 10 6 cfu/ kg DM) in in vitro evaluation (alfalfa hay and CFM, R:C= 40:60) increased IVDMD from 43.21% to 46.45% in control and probiotic groups, respectively.…”
Section: In Vitro Dry Matter Disappearance (Ivdmd%)mentioning
confidence: 97%
“…In vitro technique was done according to Tilley and Terry (1963) for one stage only (incubation with buffered rumen liquor without incubation with pepsin enzyme) for determination in vitro dry matter disappearance (IVDMD%) after different incubation periods till 96h and gas production was measured according to Cappellozza et al (2023) and Makled et al (2019).…”
Section: In Vitro Dm and Gas Production Procedurementioning
confidence: 99%
See 1 more Smart Citation